Nephrotic syndrome after allogeneic hematopoietic stem cell transplantation as a late complication of chronic graft-versus-host disease in three children - Eker, Nebil; Doğru, Ömer; Tayfun, Funda; Uygun, Vedat; Hazar, Volkan; Yeşilipek, Mehmet Akif; Küpesiz, Osman Alphan (Nature Publishing Group, 2014)
[Abstract Not Available]
Keywords: Versus; Stem Cell Transplantation; Nephrotic Syndrome